An in-vitro urinary catheterization model that approximates clinical conditions for evaluation of innovations to prevent catheter-associated urinary tract infections. Issue 1 (September 2017) - Chua, R.Y.R.; Lim, K.; Leong, S.S.J.; Tambyah, P.A.; Ho, B.
Summary: Background: Catheter-associated urinary tract infections (CAUTI) account for approximately 25% of nosocomial infections globally, and often result in increased morbidity and healthcare costs. An additional concern is the presence of microbial biofilms which are major reservoirs of bacteria, especially antibiotic-resistant bacteria, in catheters. Since introduction of the use of closed drainage systems, innovations to combat CAUTI have not led to significant improvements in clinical outcomes. The lack of a robust laboratory platform to test new CAUTI preventive strategies may impede development of novel technologies. Aim: To establish an in-vitro catheterization model (IVCM) for testing of technological innovations to prevent CAUTI. Methods: The IVCM consists of a continuous supply of urine medium flowing into a receptacle (bladder) where the urine is drained through a urinary catheter connected to an effluent collection vessel (drainage bag). Test organism(s) can be introduced conveniently into the bladder via a rubber septa port. Development of bacteriuria and microbial biofilm on the catheter can be determined subsequently. Findings: With an initial inoculum of Escherichia coli [∼5×10 5 colony-forming units (cfu)/mL] into the bladder, a 100% silicone catheter and a commercially available silver-hydrogel catheter showed heavy biofilm colonization (∼10 8 cfu/cm and ∼10 7 cfu/cm, respectively) with similar bacterial populations in the urine (bacteriuria) (∼10 8 cfu/mL and ∼10 7 cfu/mL, respectively) within three days. Interestingly, an antimicrobial peptide (CP11-6A)-coated catheter showed negligible biofilm colonization and no detectable bacteriuria. Conclusion: The IVCM is a useful preclinical approach to evaluate new strategies for the prevention of CAUTI.